Fractures in the Setting of Constriction Band Syndrome: A Case Series of Three Patients with Extremity Fractures at the Site of a Constriction Band - Yerin Cho; Leeann Qubain; Melissa Esparza; Judson Karlen; Timothy Schaub; Mohan V Belthur (MDPI AG, 2022)
Constriction band syndrome (CBS) is a rare condition where fibrous bands constrict one or more parts of the fetus with varying manifestations such as autoamputation, acrosyndactyly, and neuropathy. However, isolated extremity fractures in the setting of constriction band syndrome are even more rare, with only two reported cases in the literature. There are few guidelines on the management of CBS due to small case numbers, the variability of presentation between patients, and the lack of consensus on etiology and pathogenesis. In this small case series, we describe the presentation and management of three patients at our institution with extremity fractures at the site of severe constriction bands with neurologic injuries or vascular compromise. We also review the literature on this topic to provide further context. Intramedullary stabilization of the fracture with a k-wire allowed for soft tissue healing in two of our patients.